Alcohol: from Mesopotamia to Modern Iraq. Issue 3 (2nd August 2021) - Al Ansari, Mustafa; Dawson, Angela; Conigrave, Kate
Abstract: An understanding of alcohol's place in Iraq's history and society can help inform alcohol policy responses in that country and other Muslim majority countries. This article describes the history of alcohol in Iraq from ancient to modern times, with reflection on the challenges facing Iraqi youth today. A search was undertaken to identify peer-reviewed and gray literature that describes alcohol-related practices, norms, and values across the millennia in Iraq. A historical overview is provided of alcohol's use and context, with more detail on recent times. Alcohol was an important commodity in Iraq until the rise of Islam in the seventh century CE. Despite the subsequent Islamic restrictions on alcohol, alcohol remained present in Iraq's society and cultures. Recent studies provide varying descriptions of the prevalence of alcohol consumption, and there are challenges in researching this sensitive topic. External forces shaping alcohol use in Iraq include direct and indirect alcohol promotion, globalized media, and conflict and violence with its associated stress and trauma. Alcohol research and policy development in Iraq must consider the country's unique cultural, religious, historical, and political context. Iraq's youth may be subject to pressures to increase consumption, and thus policies must be informed by an understanding of the complex set of current perspectives and pressures.